Circular RNA CircFndc3b modulates cardiac repair after myocardial infarction via FUS/VEGF-A axis - Venkata Naga Srikanth Garikipati (Nature Portfolio, 2019)
Circular RNAs (circRNAs) are non-coding RNAs generated from pre-mRNAs of coding genes by the splicing machinery whose function in the heart is poorly understood. Here the authors show that AAV-mediated delivery of the circRNA circFndc3b prevents cardiomyocyte apoptosis, enhances angiogenesis, and attenuates LV dysfunction post-MI in mice by regulating FUS-VEGF-A signalling.